(untitled) (Journal of Pharmaceutical Negative Results, 2022)
When an infectious disease spreads, healthcare professionals debate the extent of awareness and concern. Nursing students experienced worry and stress due to clinical procedures throughout the outbreak. This study examines the knowledge of Saudi nursing students and anxiety levels undergoing clinical training at the medical departments during the COVID-19 pandemic. Methods: One hundred eighty-five nursing students at the nursing college Qassim university. A cross-sectional correlational research design was carried out in February 2020. The Generalized Anxiety Disorder 7-Item Scale (GAD-7) was used to measure anxiety in the survey, and data on sociodemographic characteristics and knowledge of COVID-19 were also obtained. Results: The results displayed that the majority of nursing students in the clinical practice (65.4%) were a high level of knowledge, 20 % did not report any anxiety at all, more than one-third experienced 39.5% moderate anxiety and less than a third experience 30. 3% have mild anxiety, and 10.3% experience severe anxiety towards the COVID-19 pandemic in clinical practice. There is a significant negative correlation between knowledge level and anxiety score (r=-–0.189, p = 0.010). Conclusions: The findings showed that most nursing students participating in clinical practice (65.4%) had a high degree of knowledge, 20% had no anxiety, more than one-third had mild anxiety, 39.5% had moderate anxiety, and fewer than one-third had severe anxiety. In the therapeutic setting, the COVID-19 pandemic causes mild anxiety in 30.3% of people and severe anxiety in 10.3%. Knowledge level and anxiety score have a substantial negative link (r=—0.189, p = 0.010).